Analysis of the Physiognomy of Unique Sets in the Maximum Number of Repetitions Strategy—The Case of One-Arm Scott Machine Seated Bicep Curls - Petre, Ioana Mădălina; Boscoianu, M.; Oancea, B; Chicomban, M.; Turcu, I; Simion, G (Applied Sciences MDPI, 2022)
The aimof this paper is to analyze the physiognomy of unique sets in the maximum number of repetitions (MNR) strategy and different correlations between the maximal forces, duration and volume for a relevant exercise in the case of a small muscle group. The research methodology proposes testing, in two phases, a total of 30 male students, for bicep curl exercises carried out on a bicep Scott machine. The obtained results showed that there were significant differences between the maximum forces (Fmax) developed during the initial and final repetitions of the exercise sets or for different machine loads. There was a large correlation between the load and Fmax and an inverse correlation between the load and MNR or between the MNR and Fmax. The deterioration of the execution mode, represented by the profile of the final repetition of high-duration sets, was also tested and analyzed. We concluded that the study of the physiognomy of cycles and comparisons at the level of relevant repetitions have revealed new perspectives for the design of periodization strategies, for the possibility of manipulating adapted muscular response or compensatory acceleration training for small muscle groups or the MNR strategy.
Keywords: maximum number of repetitions strategy; Scott machine seated bicep curl; maximal forces; compensatory acceleration training